A note to our paper “Automorphisms of homogeneous symmetric groups and hierarchomorphisms of rooted trees” - Lavrenyuk, Y.V.; Sushchansky, V.I. (Algebra and Discrete Mathematics, 2005)
The results on automorphisms of homogeneous
alternating groups are corrected and improved.